Evaluating The Effectiveness of The 'Guess Who/What' Game in Improving EFL Students' Speaking Skills - Rery, Nurul Masyithah; Putri, Hikmah Zalifah; Agustiani, Aulia (Universitas Pahlawan Tuanku Tambusai, 2025)
Speaking is a critical skill in English as a Foreign Language (EFL) learning, yet many learners face challenges in fluency, accuracy, vocabulary, and pronunciation. This study investigates the effectiveness of the